Peran Kisah Orang Saleh dalam Membangun Karakter Religius Mahasiswa di Perguruan Tinggi - Sa’idah, Futihatu; Fitriani, Adinda Naura Zahra; Almadani, Teguh (TSAQOFAH, 2025)
This study aims to examine the role of narratives about ṣāliḥ (pious) individuals in shaping the religious character of university students, particularly in the context of globalization and the overwhelming flow of digital information, which may trigger a crisis in spiritual and moral values. Using a descriptive qualitative approach, data were collected through interviews, observations of religious activities, and documentation of digital Islamic content. The findings indicate that stories of ṣāliḥ individuals serve as effective media for instilling religious values, strengthening religious identity, and fostering positive behavior and motivation among students. Storytelling by lecturers and the use of social media were found to emotionally engage students, facilitating deeper internalization of moral messages. These narratives function as uswah ḥasanah (exemplary models) that are relevant and applicable to daily life. The study concludes that integrating stories of pious individuals into Islamic higher education learning and religious development programs plays a vital role in reinforcing students' religious character. The implication is that this approach can serve as a contextual moral education strategy that meaningfully addresses the affective domain.